The Strategy of WALHI JATIM to Mitigate the Environmental Crisis through ‘School of Ecology’ in East Java - Abdul Basir Donny Polanunu; Aurora Aziza More (Global Local Interactions: Journal of International Relations, 2022)
This article explains how WALHI JATIM is working with the community to reach one of the Sustainable Development Goals (SDGs). An intermestic approach with a network model will help explain that this is a way for the people involved to take responsibility for achieving common goals. The shift in the Sustainable Development Goals agenda's focus, which calls for more people to be involved, makes the participants more diverse. This is because the ratifying state agreed to work toward universal goals for sustainable development. One of the targets for this goal is how to deal with climate change. People's lives are becoming more and more troubled by the fact that the needs of human life aren't always met by what nature has to offer. People's lives are not the only thing affected by the unrest in Indonesia. It is also clear that people are doing things that hurt the health of the environment. Conditions in the environment that haven't yet reached national standards have finally sparked community or group movements, with the argument that people are worried about the crisis of important environmental aspects and want to see the environment improve. When you look at what the community did, one of the more interesting things was what WALHI JATIM did, which was to start an School of Ecology as its first action.